The midnight train [large type] - Haig, Matt, 1975- (Random House Large Print, 2026)
"When your life flashes before your eyes, what will matter most? For Wilbur it was his time with Maggie, the love of his life. Their honeymoon in Venice, Before he threw it all away. Years later, on the brink of his own death, a train arrives. It can take Wilbur back in time to relive his most important moments. Soon, he realizes just how much he would have changed....But is it already too late?" -- Back cover.